1998
DOI: 10.1038/nm0898-923
|View full text |Cite
|
Sign up to set email alerts
|

Absence of host plasminogen activator inhibitor 1 prevents cancer invasion and vascularization

Abstract: Acquisition of invasive/metastatic potential through protease expression is an essential event in tumor progression. High levels of components of the plasminogen activation system, including urokinase, but paradoxically also its inhibitor, plasminogen activator inhibitor 1 (PAI1), have been correlated with a poor prognosis for some cancers. We report here that deficient PAI1 expression in host mice prevented local invasion and tumor vascularization of transplanted malignant keratinocytes. When this PAI1 defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

36
478
0
12

Year Published

1999
1999
2003
2003

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 623 publications
(526 citation statements)
references
References 33 publications
36
478
0
12
Order By: Relevance
“…This pathogenic effect of PAI-1 in cancer aggressiveness was confirmed by the report that cancer invasion and neovascularisation are abolished in PAI-1-deficient mice, and can be restored by local induction of PAI-1 expression (Bajou et al, 1998). This increase in PAI-1 allows a critical balance of u-PA associated to its cell surface receptor, as it could represent a key molecule in the rapid attachment/detachment events occurring at the cell leading edge that are required for migration.…”
Section: Discussionmentioning
confidence: 56%
“…This pathogenic effect of PAI-1 in cancer aggressiveness was confirmed by the report that cancer invasion and neovascularisation are abolished in PAI-1-deficient mice, and can be restored by local induction of PAI-1 expression (Bajou et al, 1998). This increase in PAI-1 allows a critical balance of u-PA associated to its cell surface receptor, as it could represent a key molecule in the rapid attachment/detachment events occurring at the cell leading edge that are required for migration.…”
Section: Discussionmentioning
confidence: 56%
“…This could further facilitate the capillary networking of the new tumour blood vessels. Accordingly, it has been reported that tumour angiogenesis is drastically impaired in mice with targeted disruption of the PAI-1 gene (Bajou et al, 1998. A few other model system studies have also suggested a proangiogenic role of PAI-1 (Lambert et al, 2001;McMahon et al, 2001;Devy et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In several cell culture and animal model systems, PAI-1 has been found to have a proangiogenic effect (Bajou et al, 1998Lambert et al, 2001;McMahon et al, 2001;Devy et al, 2002). However, the clinical significance of the biological interaction of angiogenesis and the plasminogen activator system is unknown.…”
mentioning
confidence: 99%
“…For example, host de®ciency for the plasminogen activator inhibitor (PAI1), paradoxically prevented tumor invasion and angiogenesis of malignant keratinocyte but not melanoma tumor cell xenografts (Bajou et al, 1998). This could re¯ect a requirement for the serine protease plasminogen during the neovascularization process.…”
Section: Cellular Behaviors Associated With Metastasis: Adhesion Motmentioning
confidence: 99%